Case Report: Bullous Lung Disease Following COVID-19 - Pednekar, Prachi; Amoah, Kwesi; Homer, Robert; Ryu, Changwan; Lutchmansingh, Denyse D. (Frontiers in Medicine, 2021)
More than 87% of patients report the persistence of at least one symptom after recovery from Coronavirus disease 2019 (COVID-19). Dyspnea is one of the most frequently reported symptoms following severe acute respiratory syndrome coronavirus-2 infection (SARS CoV-2) with persistent chest radiological abnormalities up to three months after symptom onset. These radiological abnormalities are variable and most commonly include ground-glass opacities, reticulations, mosaic attenuation, parenchymal bands, interlobular septal thickening, bronchiectasis, and fibrotic like changes. However, in this case report, we describe findings of bullous lung disease as a complication of severe acute respiratory syndrome coronavirus-2 infection. As the pandemic continues there is a need to understand the multiple respiratory manifestations of post-acute sequelae of COVID-19. We, therefore, present this case to add to the current body of literature describing pulmonary disease as a consequence of SARS CoV-2 infection.